Step 1: Substitute \( x = 0 \) into the expression
First, substitute \( x = 0 \) into the expression to check if the limit can be directly evaluated:
\[
\frac{\sqrt{0+1}}{\ln(0+1)} = \frac{1}{\ln(1)}.
\]
Since \( \ln(1) = 0 \), the expression becomes \( \frac{1}{0} \), which is undefined. This indicates that the limit cannot be directly evaluated and requires further analysis.
Step 2: Apply L'Hôpital's Rule
Since substituting \( x = 0 \) results in an indeterminate form \( \frac{1}{0} \), we can use L'Hôpital's Rule. L'Hôpital's Rule states that if:
\[
\lim_{x \to a} \frac{f(x)}{g(x)} = \frac{0}{0} \text{ or } \frac{\infty}{\infty},
\]
then:
\[
\lim_{x \to a} \frac{f(x)}{g(x)} = \lim_{x \to a} \frac{f'(x)}{g'(x)},
\]
provided the limit on the right exists.